IMPROVING THE SINGING SKILLS WITH THE GUIDED TRAINING METHOD IN CLASS III SDN 3 KOTA RINDAU - Lagandesa Yun Ratna (Education Journal, 2020)
This study aims to improve student learning outcomes in the learning of the Cultural Skills in third grade students of SDN 3 rindau city. This type of research is classroom action research (CAR). The subjects of this study were 27 people consisting of 14 male students and 13 female students and the data obtained were qualitative and quantitative data. The object of the study was the results of the Skillful Student's Learning outcomes using the guided training method. The results of the study by improving student learning outcomes using the guided training method in the subject of Articulture Skills in class III SDN 3 Rindau City increased from cycle I to cycle II. That the initial test of students obtained data with an average value of 59.87% and classical completeness of 39.50% while in the first cycle data obtained an average value of students 66.72% and classical completeness of 59.26% while in Silkus II the average value the average students gained 83.26% and the classical mastery was 98.76%. By looking at the development of research in each cycle that the value of students has increased, it can be concluded that research using the exercise method can improve the ability to sing national compulsory songs of third grade students at SDN 3 City ridau in the subject of the Skill of the Cultural Skills.